2014
DOI: 10.2147/ijn.s63064
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology of antimicrobial nanoparticlesfor prosthetic devices

Abstract: Advances in nanotechnology are producing an accelerated proliferation of new nanomaterial composites that are likely to become an important source of engineered health-related products. Nanoparticles with antifungal effects are of great interest in the formulation of microbicidal materials. Fungi are found as innocuous commensals and colonize various habitats in and on humans, especially the skin and mucosa. As growth on surfaces is a natural part of the Candida spp. lifestyle, one can e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 81 publications
1
7
0
Order By: Relevance
“…These results are similar to that achieved by Paszek et al [52], at which the cytotoxic effect on human endothelial cells of blood vessels were observed at the ZnO NPs concentration of 30 mg/L. Numerous studies indicate that the MTT assay may underestimate a compound’s cytotoxicity by overestimating the cell viability, and therefore cytotoxicity testing by the MTT assay should be supported by another assay to analyze possible toxicological effects of nanocompounds [57]. Accordingly, microscopic imaging of the HeLa cells treated with ZnO NPs was performed.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results are similar to that achieved by Paszek et al [52], at which the cytotoxic effect on human endothelial cells of blood vessels were observed at the ZnO NPs concentration of 30 mg/L. Numerous studies indicate that the MTT assay may underestimate a compound’s cytotoxicity by overestimating the cell viability, and therefore cytotoxicity testing by the MTT assay should be supported by another assay to analyze possible toxicological effects of nanocompounds [57]. Accordingly, microscopic imaging of the HeLa cells treated with ZnO NPs was performed.…”
Section: Discussionsupporting
confidence: 87%
“…Simultaneously with the MTT assay, microscopic imaging of the HeLa cells treated with ZnO NPs was performed. These microscopic observations were performed to verify the results of the MTT assay, which may be unreliable in the case of the cytotoxicity studies of some nanoparticles [57]. The microscopic observation revealed that the morphology of the cells and the structure of the cell monolayer did not differ in the control group and the cells treated with 1, 6, 10, 20, and 30 mg/L ZnO NPs (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…As stated in previous sections of this review paper, NPs facilitate the penetration and delivery of antimicrobial agents into biological membranes including microbial cells, thereby enhancing and increasing biological activities [ 76 , 113 ]. This means that the toxicity of different NP-antimicrobial polymers needs a time-dependent understanding and characterization [ 125 ]. Generally, antimicrobial agents’ biocompatibility inhibition cannot occur without producing some undesirable health effects, either local or systemic.…”
Section: Nanoparticles Toxicitymentioning
confidence: 99%
“…The advances in polymer technology have produced novel polymers such as high-impact polymers and fiber-reinforced polymers with improved impact strength and fatigue resistance. The polymer modifications are achieved either by incorporating additives such as rubber,[10] styrene-butadiene,[11] Al 2 O 3 ,[12] and β-AgVO 3 [13] or by adding inorganic fillers such as metallic oxides,[14] fluorinated glass fillers,[15] hydroxyapatite whiskers,[16] zirconia,[17] and organic fibers[18] of carbon/graphite, aramid, ultra-high modulus polyethylene, nylon, and jute. Reviews of studies regarding the polymeric modifications are available in the dental literature.…”
Section: Introductionmentioning
confidence: 99%